The dual roles of human PYHIN family proteins in cancer: mechanisms and therapeutic implications - Zeng, Shuyan; Zhou, Zhiyong; Li, Yi; Wu, Di; Xiao, Qiuyun; Peng, Huiyun (Frontiers in Immunology, 2025)
The human PYHIN family proteins, including AIM2, IFI16, IFIX, and MNDA, which are crucial cytosolic nucleic acid sensors. These proteins share a common structural feature, including signature N-terminal PYD domain and C-terminal HIN-200 domain, which enable them to recognize intracellular nucleic acids and assemble inflammasomes, triggering inflammatory responses and programmed cell death. Over the last decade, it has emerged that the PYHIN family proteins play multifaceted roles in cancer biology, with dualistic roles due to tumor heterogeneity and the tumor microenvironment’s plasticity through dependent or independent of inflammasome mechanisms. Here, we discuss their ability to function as both a tumor suppressor and a tumor promoter of tumor progression emphasizes the need for further research to delineate the precise mechanisms by which these proteins operate in various cancer contexts. Understanding these dynamics could pave the way for novel therapeutic approaches that harness the dual nature of PYHIN family members to improve cancer treatment outcomes.